History and teaching of behavior analysis in Bahia: from the creation of the experimental laboratory to the training of the first behavior analysts at FFCH/UFBA (1968-1980) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The objective is to describe and analyze the process of implantation of the experimental laboratory and the formation of the first behavior analysts of the FFCH/UFBA psychology course. The initial milestones of Behavior Analysis in Brazil are presented; the process of creating the laboratory for the FFCH/UFBA psychology course; and the training of the first behavior analysts in Salvador, between 1968 and 1980. The perspective of the Social Studies of Sciences and the Critical History of Psychology is adopted. The primary sources accessed from the UFBA archives were: minutes, opinions, letters, official letters, course programs, lesson plans and reports. It was verified that the experimental psychology laboratory was structured from the theoretical-technical support of the psychologists of the AEC of the USP and that the reception to the AEC in the course of the UFBA met the demands of teaching and training teachers and students in the academic context of Bahia, in the analyzed period.
Keywords: history of psychology in Bahia; history of behavior analysis; experimental psychology laboratory